Association between expression of intercellular adhesion molecule‐1 and integration of human T‐cell‐leukemia virus type 1 in adult T‐cell leukemia cells - Motoya, Satoshi (J Clin Lab Anal, 1998)
It is known that the expression levels of intercellular adhesion molecule‐1 (ICAM‐1) in adult T cell leukemia(ATL) cells are high, whereas those in T‐lymphoid cells are not. In order to investigate the factors that influence the induction of ICAM‐1 molecules, Northern blot analysis to measure the expression level of ICAM‐1 mRNAs and Southern blot hybridization to analyze the integration of human T‐cell‐leukemia virus type 1 (HTLV‐1) provirus were done. The levels of ICAM‐1 mRNA expression of ATL cells were generally higher than those of T‐lymphoid cells. However, ILT‐mat cells and ATL16T(‐) cells, although they were ATL cells, showed rather low surface ICAM‐1 expression and ICAM‐1 mRNA expression. Southern blot hybridization showed that only two and four bands were found in ILT‐mat and ATL16T(‐) cells, respectively, whereas >10 bands were detected in other ATL cells. These results suggest that monoclonal integration of HTLV‐1 provirus to the genome of T cell, especially the number of integration sites, is one of the factors for induction of ICAM‐1 molecules. J. Clin. Lab. Anal. 11:186–189, 1997. © 1997 Wiley‐Liss, Inc.